VIROTHERAPY TARGETING BREAST CANCER STEMS CELLS BY USING ONCOLYTIC HERPS SIMPLEX VIRUS. - MAYTHAM ABBAS ABBODI (International Journal of Pharma and Bio Sciences, 2013)
In the present study I isolated breast cancer stem cells from cell line MDA-MB231 by used CD44 MicroBeads separator. Cancer stem cells (CSCs) were identified by used PCR machine; here specific primers were designed for CD44 and CD24 genes, whereas CD44 positive for breast CSCs and CD24 negative CSCs. MDA-MB231 cells and breast CSCs treated with G47Δ vector. G47Δ showed highly effect on both kinds of cells by killing over 90% of MDA-MB231 and over 80% of the CSCs in vitro. Virus used as therapy demonstrated that pathogenic microorganisms can be modify genetically and use for targeting diseases and oHSV can be used for treatment breast CSCs that are still not understood. This study demonstrates that oHVS effective against breast cancer stem cells and could be a beneficial method for treating cancer stem cells expressed in breast cancer.